Obchody dwudziestopięciolecia kinematografii Dolnego Śląska w 1970 roku - Andrzej Dębski (Studia Filmoznawcze)
The purpose of this article was to look at film culture in Lower Silesia in 1970 and the starting point was the brochure ‘XXV years of cinematography of Lower Silesia’. The plans indicated in the brochure were confronted with their realization, for which aim the Lower Silesian press and archival records were analyzed. Since the brochure presents actions that fit into the ideological and cultural agenda, the article also takes a closer look at the activities of cinemas at that time, which indicate that the viewers preferred Western films and disliked Soviet films the most.